2017
DOI: 10.1039/c7ob00897j
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis and biological evaluation of enantiomerically pure tricyclic indolines

Abstract: Tricyclic indolines are common in both natural products and synthetic chemical probes. In this study we demonstrated that enantiomerically pure tricyclic indolines can be prepared from an inexpensive commmercially available chiral starting material, pyroglutamic acid. The synthesis features a highly diastereoselective gold-catalyzed cyclization of alkyne-tethered indoles and subsequent diastereoselective reductive ring-opening reaction. Using this approach, we synthesized analogs of our previously discovered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Methods for the dearomatization of indole derivatives using electrophilic reagents are well established, and the idea to trap the resulting products (usually indolenines) with a tethered nucleophile is also known; for example, Bandini et al demonstrated the power of this approach for the conversion of indole-tethered propargyl alcohols 14 into tetracyclic fused furoindolines 15 using a gold-catalyzed cyclization cascade (Scheme a) . Indeed, a similar strategy has also been used for the assembly of tetracyclic alkaloid scaffolds 17 via alkyne activation, exemplified by a gold­(I)-catalyzed system reported by Wang et al (Scheme b); the same group also demonstrated the value of this method in the formal synthesis of minfiensine and used it for the generation of medicinally relevant scaffolds . Methods to prepare enantioenriched scaffolds in this way are less well established, and are most commonly achieved via transition-metal catalyzed asymmetric allylation reactions, exemplified by Jiao’s study summarized in Scheme c…”
mentioning
confidence: 99%
“…Methods for the dearomatization of indole derivatives using electrophilic reagents are well established, and the idea to trap the resulting products (usually indolenines) with a tethered nucleophile is also known; for example, Bandini et al demonstrated the power of this approach for the conversion of indole-tethered propargyl alcohols 14 into tetracyclic fused furoindolines 15 using a gold-catalyzed cyclization cascade (Scheme a) . Indeed, a similar strategy has also been used for the assembly of tetracyclic alkaloid scaffolds 17 via alkyne activation, exemplified by a gold­(I)-catalyzed system reported by Wang et al (Scheme b); the same group also demonstrated the value of this method in the formal synthesis of minfiensine and used it for the generation of medicinally relevant scaffolds . Methods to prepare enantioenriched scaffolds in this way are less well established, and are most commonly achieved via transition-metal catalyzed asymmetric allylation reactions, exemplified by Jiao’s study summarized in Scheme c…”
mentioning
confidence: 99%
“…In this series we synthesized four esters of pyroglutamic acid, viz. methyl, ethyl, iso -propyl ( 1 ), and tert -butyl ( 2 ). The methyl and ethyl ester could only be recovered as oils, while 1 and 2 could be crystallized, followed by the determination of their X-ray structure.…”
Section: Resultsmentioning
confidence: 99%